Light Pollution and Smart Outdoor Lighting - (:unkn) unknown (My University, 2021)
With the developing technology and increasing_x000D_ urbanization, many problems have started to arise in the use of_x000D_ energy resources and nature. In addition to environmental_x000D_ effects, energy-saving considerations constitute the main purpose_x000D_ of any proposed smart system. In outdoor lighting, along with the_x000D_ use of energy-efficient bulbs, the lighting should be done with the_x000D_ right method and the right way. In addition to these, an_x000D_ intelligent system integrated with an automatic control_x000D_ mechanism is needed. Incorrect outdoor lighting causes_x000D_ unnecessary energy consumption as well as light pollution and_x000D_ CO2 emission. These situations have negative consequences on_x000D_ both mental and physical health of the human, as well as on other_x000D_ living creatures and nature. Therefore, smart outdoor lighting_x000D_ systems offer an essential solution in preventing negative_x000D_ consequences that may occur with incorrect outdoor lighting._x000D_ In this study, outdoor lighting requirements, light pollution and_x000D_ smart cities are examined in detail and the smart outdoor lighting_x000D_ systems within the scope of the smart cities are emphasized. As a_x000D_ result, the importance and necessity of the smart outdoor lighting_x000D_ system which provides energy-efficient and environmentally_x000D_ friendly structures by enabling street lamps to work smartly and_x000D_ efficiently are outlined.